Effects of woody plant encroachment on abundance of multiple tick species in the U.S. Great Plains - Jozlyn Propst; Tucker Taylor; Scott R. Loss; Bruce H. Noden (PLoS ONE, 2025)
Vector-borne diseases are increasing in prevalence, posing a risk to 80% of the human population worldwide. In the United States, tick-borne diseases account for 75% of all nationally reported vector-borne disease cases. As the distribution of medically important ticks and tick-borne diseases increases, it is crucial to understand the factors driving their expansion. Changes in land cover are a known driver of vector-borne disease emergence and prevalence. In the U.S. Great Plains, a dominant form of land cover change affecting vectors and vector-borne diseases is woody plant encroachment (WPE), the expansion of trees and shrubs into grassland ecosystems due to fire suppression and other anthropogenic factors. In this study, we examined whether WPE by eastern redcedar (Juniperus virginiana, ERC), a widespread encroaching tree in the Great Plains, influences abundance of three medically important tick species, Amblyomma americanum, Dermacentor variabilis, and Amblyomma maculatum. Through CO2 trapping and flagging, we collected ticks in Oklahoma, USA, in sites capturing open grasslands and three intensifying stages of ERC encroachment. For all analyses, we found that abundances of A. americanum and D. variabilis were higher in the earliest stage of ERC encroachment compared to open grassland, indicating that abundances of these species increase shortly after the onset of encroachment. However, for A. maculatum, a species known to be associated with grassland ecosystems, abundance was lower in areas experiencing ERC encroachment compared to grasslands. Our results suggest that the most effective strategy to managing tick populations in association with WPE is to prevent ERC encroachment entirely or to remove encroachment early on before progression to later stages. Landowners, managers of public and private lands, and public health officials should be aware of the health risks associated with ERC encroachment and consider initiating educational and management protocols to protect their communities.